A liquid chromatography method for determination of pyrethroids insecticides residues in beans - Monteiro, Sérgio Henrique; Ciscato, Cláudia Helena Pastor; Gebara, Amir Bertoni; Masini, Jorge Cesar (Eclética Química, 2014)
A rapid liquid chromatographic (LC) method was developed for simultaneous determination of 7 pyrethroid insecticides in beans. Residues were extracted from beans with acetone, followed by partition with ethyl acetate/cyclohexane (1+1) and clean up by gel-permeation chromatography. LC separation was performed on a LiChrospher 100 RP-18 column using acetonitrile/water (8+2) as mobile phase. The pesticides were detected by molecular absorption spectrophotometry at 212 nm. Recoveries of 7 pyrethroids fortified at 0.010; 0.10; 1.0 mg kg-1 levels were within the range 71-105 %. Advantageous features of this method are: the quantification limits, which were between 0.004 and 0.011 mg kg-1, and the simplicity in the sample treatment, which requires less clean-up if compared with the GC-ECD determination. No residues of pyrethroids were detected in 48 bean samples commercialized in São Paulo City during 2008.